"E deu nome a todas as coisas": as relações entre violência, território e desenvolvimento na formação da Zona Rural II de São Luís, Maranhão (1996-2015) - Sbrana, Tayanná Santos de Jesus (2017)
This study aims to understand the formation of the Zona Rural II of São Luís as a territory of conflicts, in the period between 1996 – the year in which discussions begin on the implementation of a conservation unit as a territorial safeguard alternative for twelve communities auto identified as traditional (Rio dos Cachorros, Taim, Limoeiro, Porto Grande, Jacamim, Porto das Arraias, Parnauaçu, Jacamim, Portinho, Embaubal, Ilha Pequena, Amapá and Tauá-Mirim), in response to the expulsion processes derived from development projects, such as the Programa Grande Carajás (1980) – and 2015 – year in which these communities institute the Extractive Reserve of Tauá-Mirim. We seek to understand how communities, business and governmental managers enter into conflicts on the same territory (Zona Rural II de São Luís - MA), from different projects for region, such as RESEX or as Industrial District (DISAL), and how they do strategies within these groups in opposition or articulation between sectors. We analyze, therefore, oral sources (interviews, recordings of lectures and other public manifestations), written documentation (reports, opinions and judicial processes) and bibliography, carrying out fieldwork, collecting the sources and their conjugated analysis, and bibliographical review for theoretical leveling.